Enhancements of the production of bilirubin and the expression of β‐globin by carbon monoxide during erythroid differentiation. Issue 10 (18th May 2016) - Mu, Anfeng; Li, Ming; Tanaka, Masakazu; Adachi, Yasushi; Tai, Tran Tien; Liem, Pham Hieu; Izawa, Shingo; Furuyama, Kazumichi; Taketani, Shigeru
Abstract : Heme is degraded by heme oxygenase to form iron, carbon monoxide (CO), and biliverdin. However, information about the catabolism of heme in erythroid cells is limited. In this study, we showed the production and export of bilirubin in murine erythroleukemia (MEL) cells. The production of bilirubin by MEL cells was enhanced when heme synthesis was induced. When mouse bone marrow cells were induced with erythropoietin to differentiate into erythroid cells, the synthesis of bilirubin increased. The expression of β‐globin was enhanced by CO at the transcriptional level. These results indicate that constant production of CO from heme regulates erythropoiesis. Abstract :